The Potential Demand for and Strategic Use of an HIV-1 Vaccine in Southern India - Seshadri, Shreelata Rao; Subramaniyam, P.; Jha, Prabhat (World Bank, Washington, DC, 2014)
Even a modestly effective HIV-1 vaccine would be highly useful in India and could avoid millions of deaths. How should such a vaccine be introduced? Based on evidence of adoption of other vaccines in India, current levels of spending on them and coverage of prevention programs targeting both high- and low-risk groups, Seshadri, Subramaniyam, and Jha assess the potential demand for and strategic use of an HIV-1 vaccine in the four southern Indian states of Andhra Pradesh, Karnataka, Maharashtra, and Tamil Nadu. The authors also discuss potential strategies for delivery of the vaccine, prioritization for vaccination, and the political economy of such a vaccine in India. Assuming a vaccine cost of $10 a dose and including estimated delivery costs, the total cost of vaccinating 21.6 million adolescents 11-14 years of age and 1 percent of adults would be Rs. 12.25 billion (US$ 245 million). To maintain the vaccination rate in the 11-14 year old cohort, an additional 6.77 million in that age range would have to be vaccinated each year, at a vaccine cost of Rs. 3.39 billion (US$ 67.5 million). An HIV-1 vaccine will greatly reduce HIV/AIDS in India, but it will not be a panacea. There will be a continued need for effective prevention programs to guard against behavior reversals or an imperfect vaccine. Key inputs for prevention, immunization, and treatment programs such as identification of various groups that could be immunized (vulnerable groups or general populations), strengthened surveillance, capacity building, operations research, and evaluation at local levels will continue to require intensive support.